Multiple sclerosis: know to better care - Zuila Maria de Figueiredo Carvalho; Priscila Alencar Mendes; Layana de Paula Cavalcante; Maria Goretti Soares Monteiro; Jacqueline Dantas Sampaio; Maria Corina Amaral Viana (Universidad de Alicante, 2012)
The study shows the care and pathophysiological aspects of multiple sclerosis. It aims to report the knowledge acquired by nursing students on the care, specifically of people with multiple sclerosis caused disabilities and also provide nursing interventions that might help in promoting the welfare and improving the life quality. This is a case study, based on data collected through interviews, physical examination and search on records in a systematic way to identify problems. The results are presented in the form of clinical history, diagnoses and planning care for a female patient who developed the disease. The experience presented herein provides evidence that describing the basics of nursing care perceived and implemented by students, guided and supervised by teachers of nursing, is a tool in teaching and learning of caring.